Vulnerability, family violence and institutionalization: narratives for elderly and professionals in social welcome center - Dayane Akinara Toledo Ribeiro; Aline Balandis Costa; Pâmela Patricia Mariano; Vanessa Denardi Antoniassi Baldissera; Susanne Elero Betioli; Lígia Carreira (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To know the institutionalization process and the functional clinical condition of elderly people who suffered family violence, from the perspective of the elderly and professionals. Methods Qualitative, which used oral history as a data collection technique. Held in a long-term institution for the elderly, using a semi-structured interview script. The participants were three nursing technicians, two nursing assistants, five caregivers for the elderly and eight elderly. Thematic analysis was performed with the aid of the MAXQDA® software. Results Three categories were identified: The condition of vulnerability and the care needs of the elderly, indicating welcoming as an intervention; Suffering and denial of conditions of vulnerability; and Situations of family violence and the positive aspects of reception. Conclusions Long-term institutions are considered important spaces for comprehensive and humanized care, as well as essential for the protection of elderly victims of family violence.